Le rôle du droit dans la formation des élites : retour sur une thématique centrale des analyses critiques du droit - Liora Israël (Clio@Themis, 2021)
Critical legal studies have developed since the late 1970 s in several countries. All of them put at the center the question of legal education, considering its contribution to the ideological and social status quo. This heritage is precious to understand how the debate about legal education evolved, and to consider empirically – as in the research project Elidroit – the place of law in the formation and reproduction of elites from a sociological standpoint.